Dukungan Keluarga Terhadap Diet Seimbang Pada Penderita Diabetes Melitus Tipe 2 Di UPT Puskesmas Alianyang Pontianak Tahun 2025: Fransiska Romina, Yustina Riki Nazarius, Usu Sius1, Lusiana Emeliana, Debby Syahru Romadlon, Diana Barsasella - Fransiska Romina; Yustina Riki Nazarius; Usu Sius; Lusiana Emeliana; Debby Syahru Romadlon; Diana Barsasella (STIKes Persada Husada Indonesia, 2026)
Type 2 diabetes mellitus is a chronic disease that requires long-term management, including the implementation of a balanced diet. A balanced diet helps maintain blood glucose levels and prevent complications. The success of diet adherence is greatly influenced by family support, which includes emotional, instrumental, informational, and appraisal support. Lack of family support can become a barrier to patients’ compliance with healthy eating patterns. This study aims to determine the influence of family support on compliance with a balanced diet in patients with type 2 diabetes mellitus. This study used a qualitative descriptive method with a case study approach involving five families of patients with type 2 diabetes mellitus. Data were collected through in-depth interviews and direct observation of family support and patient dietary compliance. Of the five families studied, three families demonstrated positive support in the form of assistance with providing healthy food, monitoring meal schedules, and offering motivation. Patients in these families showed high adherence to a balanced diet. Meanwhile, the other two families did not provide sufficient support—they were less involved in dietary management and lacked understanding of the importance of a balanced diet. This resulted in low dietary compliance among those patients. Family support plays an important role in the successful implementation of a balanced diet in patients with type 2 diabetes mellitus. Families that are actively involved in dietary support contribute to better adherence and help prevent complications.